P27Kip1 and p21Cip1 collaborate in the regulation of transcription by recruiting cyclin–Cdk complexes on the promoters of target genes. Issue 14 (13th June 2015) - Orlando, Serena; Gallastegui, Edurne; Besson, Arnaud; Abril, Gabriel; Aligué, Rosa; Pujol, Maria Jesus; Bachs, Oriol
Abstract: Transcriptional repressor complexes containing p130 and E2F4 regulate the expression of genes involved in DNA replication. During the G1 phase of the cell cycle, sequential phosphorylation of p130 by cyclin-dependent kinases (Cdks) disrupts these complexes allowing gene expression. The Cdk inhibitor and tumor suppressor p27 Kip1 associates with p130 and E2F4 by its carboxyl domain on the promoters of target genes but its role in the regulation of transcription remains unclear. We report here that p27 Kip1 recruits cyclin D2/D3–Cdk4 complexes on the promoters by its amino terminal domain in early and mid G1 . In cells lacking p27 Kip1, cyclin D2/D3–Cdk4 did not associate to the promoters and phosphorylation of p130 and transcription of target genes was increased. In late G1, these complexes were substituted by p21 Cip1 -cyclin D1–Cdk2. In p21 Cip1 null cells cyclin D1–Cdk2 were not found on the promoters and transcription was elevated. In p21/p27 double null cells transcription was higher than in control cells and single knock out cells. Thus, our results clarify the role of p27 Kip1 and p21 Cip1 in transcriptional regulation of genes repressed by p130/E2F4 complexes in which p27 Kip1 and p21 Cip1 play a sequential role by recruiting and regulating the activity of specific cyclin–Cdk complexes on the promoters.